Histoire de Jos. Montferrand, l'athlète canadien - Sulte, Benjamin (Beauchemin, 1899)
Keywords: Montferrand; Joseph

Mère de la Nativité et les origines des soeurs de Miséricorde 1848-1898 (Imprimerie des sourds-muets, 1898)
Keywords: Communautés religieuses; Nativité; Mère de la; Soeurs de Miséricorde

Souvenir des fêtes jubilaires du Collège Sainte-Marie de Montréal, 1848-1898 (s.é., 1898)
Keywords: Collège Sainte-Marie; Communautés religieuses; Jésuites

Marie de la Nativité et les origines des soeurs de Miséricorde, 1848-1898 - Fournet, P.-A. (Imprimerie de l'Institution des sourds-muets, 1898)
Keywords: Cadron; Marie-Rosalie; Communautés religieuses; Soeurs de Miséricorde

Mother Nativity and the Origin of the Community of the Sisters of Miséricorde, 1848-1898 - Fournet, Pierre-Auguste (Institution for Deaf Mutes, 1898)
Keywords: Cadron; Marie-Rosalie; Communautés religieuses; Soeurs de Miséricorde

Historical and Descriptive Notice on the Church of Notre-Dame of Montreal (s.é., 1897)
Keywords: Notre-Dame (église); Églises

Histoire de la charité à Montréal - Germano, J. (Revue canadienne, 1896)
Tome: 9
Keywords: Communautés religieuses

Une institution nationale: la Banque du peuple (Revue canadienne, 1895)
Keywords: Banque du Peuple; Banques

Annales des religieuses de Notre-Dame de Charité du Bon-Pasteur d'Angers - Gauthier, Henri (s.é., 1895)
Keywords: Soeurs du Bon-Pasteur

La Miséricorde ou 50 années de dévouement et d'abnégation des religieuses de miséricorde à Montréal - Giroux, Henri (s.é., 1894)
Keywords: Communautés religieuses; Soeurs de Miséricorde

Notice sur les écoles relevant du bureau des commissaires catholiques romains de la cité de Montréal (Canada) (s.é., 1893)
Keywords: Commission des écoles catholiques de Montréal

Madame Gamelin et les origines de la Providence - Bourassa, Gustave (s.é., 1892)
Keywords: Communautés religieuses; Soeurs de la Providence; Tavernier; Émilie (Gamelin; Émilie)

Le Collège Sainte-Marie de Montréal - Bellay, A. (Revue canadienne, 1891)
Tome: 4
Keywords: Collège Sainte-Marie; Communautés religieuses; Jésuites

Jubilee History of Trinity Church, Montreal, 1840-1890 - Mott, Henry (s.é., 1890)
Keywords: Trinity Church; Églises

Les bourgeois de la Compagnie du Nord-Ouest - Masson, Louis-Rodrigue (Imprimerie Générale A. Côté et Cie, 1889)
Keywords: Compagnie du Nord-Ouest; Fourrure; Marchands

Chronicles of the St. James Methodist Church, Montreal, From the First Rise of Methodism in Montreal to the Laying of the Corner-Stone of the New Church on St. Catherine Street - Jaques, G. E. (William Briggs, 1888)
Keywords: Méthodistes; Protestants; St. James Methodist

A History of the Scotch Presbyterian Church, St. Gabriel Street - Campbell, Robert (W. Drysdale, 1887)
Keywords: Presbytériens; Protestants; St Gabriel Street Presbyterian Church

Mgr Jean-Jacques Lartigue, 1er évêque de Montréal (1777-1840) - Charland, J.-H. (Revue canadienne, 1887)
Keywords: Lartigue; Jean-Jacques; Évêques

Golden Jubilee of the Reverend Fathers Dowd and Toupin with Historical Sketch of Irish Community of Montreal - Curran, J. J. (Lovell, 1887)
Keywords: Dowd; Patrick; Irlandais; Toupin; Joseph

The Life of John Mockett Cramp, D.D., 1796-1881, [...] - Higgins, T.A. (Drysdale, 1887)
Keywords: Baptistes; Cramp; John Mockett; Protestants

Memoir of Henry Wilkes, D.D., LL.D., his Life and Times - Wood, John (F.E. Grafton/Holder and Stoughton, 1887)
Keywords: Congrégationalistes; Protestants; Wilkes; Henry

Notice sur les écoles relevant du bureau des commissaires catholiques romains de la cité de Montréal (Beauchemin, 1886)
Keywords: Commission des écoles catholiques de Montréal

History of the Montreal Prison from 1784 to 1886 - Borthwick, J. Douglas (A. Periard, 1886)
Keywords: Prisons

A Summary of the First Fifty Years Transactions of the St. Andrew's Society of Montreal - Campbell, Robert (McQueen et Corneil, 1886)
Keywords: Saint Andrew's Society; Écossais

Une histoire édifiante: la communauté des Soeurs de Ste-Anne - Giroux, Henri (Wilson et Coeley, 1886)
Keywords: Communautés religieuses; Soeurs de Sainte-Anne

Le P. Martin - Vignon, Firmin (s.é., 1886)
Keywords: Collège Sainte-Marie; Communautés religieuses; Jésuites; Martin; Félix

Biographies des premiers supérieurs et bienfaiteurs de l'institut des Soeurs de Charité de la Providence [...] (s.é., 1885)
issued: 1885/1903
Keywords: Soeurs de la Providence

Une héroïne du Canada: madame Gamelin et ses oeuvres - Giroux, Henri (s.é., 1885)
Keywords: Communautés religieuses; Soeurs de la Providence; Tavernier; Émilie (Gamelin; Émilie)

Historical Sketches of the Protestant Churches and Ministers of Montreal - Massey, Samuel (Witness, 1885)
Keywords: Protestants; Églises

Vie de M. Pierre-Louis Billaudèle, grand-vicaire et dixième supérieur du séminaire de Montréal - Rousseau, Pierre (Cadieux et Derome, 1885)
Keywords: Billaudèle; Pierre-Louis; Communautés religieuses; Sulpiciens

The Life of Sir William E. Logan, Kt., First Director of the Geological Survey of Canada - Harrington, Bernard James (Dawson Brothers, 1883)
Keywords: Commission géologique du Canada; Géologie; Logan; William Edmond

The Montreal Snow Shoe Club, Its History and Record.. - Becket, Hugh W. (Becket Bros., 1882)
Keywords: Clubs; Montreal Snow Shoe Club; Raquetteurs

Mémoires pour servir à l'histoire du chapitre de la cathédrale de S. Jacques de Montréal - Bourget, Ignace (s.é., 1882)
Keywords: Cathédrale; Saint-Jacques (cathédrale)

A Semicentennial Celebration. Introductory Address: A Sketch of the Life of the Late G.W. Campbell, A.M., M.D., L.L.D., Late Dean of the Medical Faculty, and a Summary of the History of the Faculty - Howard, R. P. (Gazette Printing, 1882)
Keywords: Campbell; George William; Médecine; Université McGill

M. Faillon, prêtre de St-Sulpice; sa vie et ses oeuvres - Desmazures, Adam Charles (Bibliothèque paroissiale, 1879)
Keywords: Billaudèle; Pierre-Louis; Communautés religieuses; Faillon; Étienne-Michel; Histoire; Sulpiciens

Histoire de la communauté de Notre Dame de Charité du Bon Pasteur de Montréal suivi d'une biographie de Messire J. V. Arraud, ss - Giroux, Henri (Lovell, 1879)
Keywords: Arraud; J. V.; Communautés religieuses; Soeurs du Bon-Pasteur

On the Street and Footwalk Pavements of Montreal, Canada from Year 1842 to 1878 - St George, Percival Walter (The Institute of Civil Engineers, 1879)
Keywords: Rues

Notice historique sur la vie de M. Joseph-Octave Paré - Bourget, Ignace (Imprimerie canadienne, 1878)
Keywords: Paré; Joseph-Octave

Vie de M. Faillon, prêtre de Saint-Sulpice, par l'auteur de la "Vie de M. Mollevaut" - Gamon, Firmin-Regis (J. Vic, 1877)
Keywords: Communautés religieuses; Faillon; Étienne-Michel; Sulpiciens

Vie de la mère Sainte-Madeleine, supérieure de la Congrégation de Notre-Dame de Montréal - Neream, André (E. Sénécal, 1876)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Huot; Marie-Catherine; Sainte-Madeleine; Mère

Montreal and Its Fortifications - Sandham, Alfred (Daniel Rose, 1874)
Keywords: Fortifications

Rapport sur l'agrandissement proposé de l'aqueduc de Montréal, suivi de l'historique de l'aqueduc: d'après l'ordre du Comité de l'eau - Lesage, Louis (Cité de Montréal, Comité de l'aqueduc, 1873)
Keywords: Aqueduc

Report on the proposed enlargement of the Montreal water works: together with an historical sketch of the works up to the present date: in accordance with instructions from the water committee - Lesage, Louis (City of Montreal, Water Works Committee, 1873)
Keywords: Aqueduc

History of the Montreal Young Men's Christian Association - Sandham, Alfred (s.é., 1873)
Keywords: Massey; Samuel; YMCA

Annales religieuses et historiques de la paroisse de St-Jacques le Majeur - Chagnon, F. X. (J.A. Plinguet, 1872)
Keywords: Saint-Jacques (paroisse)

James McGill and the Origin of his University - Dawson, John William (New Dominion Monthly, 1870)
Keywords: McGill; James; Université McGill

James McGill and the Origin of his University - Dawson, J. W. (s.é., 1870)
Keywords: McGill; James; Université McGill

A Short History of the Canon for the Election of a Bishop of Montreal and Metropolitan of Canada (Montreal Printing & Pub. Co., 1869)
Keywords: Anglicans; Protestants; Évêques

On Some of the Causes of the Excessive Mortality of Young Children in the City of Montreal - Carpenter, Philip P. (Canadian Naturalist and Geologist, 1869)
Keywords: Enfants; Mortalité

Montreal fifty years ago - Brown, T.S. (s.é., 1868)

The Hon. Thos. D'Arcy McGee: A Sketch of his Life and Death - Taylor, John Fennings (J. Lovell, 1868)
Keywords: Irlandais; McGee; Thomas d'Arcy

On the Past, Present, and Future of the Faculty of Medecine of McGill University; an Introductory Lecture Delivered at the Opening of the Session 1866-67 - Hall, Archibald (Canada Medical Journal and Monthly Record of Medical and Surgical Science, 1866)
Keywords: Médecine; Université McGill

Souvenirs sur les commencements de l'Union St-Joseph de Montréal - Plinguet, J. A. (Plinguet et Laplante, 1866)
Keywords: Assurance; Union Saint-Joseph

The Case of the Canadians of Montreal Distressed by Fire (s.-é., 1865)
Keywords: Incendies

A History of the Grand Trunk Railway of Canada - Brown, Thomas Storrow (Hunter, Rose, 1864)
Keywords: Chemins de fer; Grand Tronc

James McGill and the University of McGill College - Dawson, John William (Barnard's American Journal of Education, 1863)
Keywords: McGill; James; Université McGill

A Biographical Sketch of the Late A.F. Holmes, M.D., LL.D., Including a Summary History of Medical Department of McGill College - Hall, Archibald (University Medical Students' Association of McGill College, 1860)
Keywords: Holmes; Andrew Fernando; Médecine; Université McGill

Esquisse biographique sur Chevalier de Lorimier - Fabre, Hector (Imprimerie du "Pays", 1856)
Keywords: Lorimier; Chevalier de; Notaires; Rébellions

Retrospective Glance at the Progressive State of the Natural History Society of Montreal, with a View to Ascertaining how Far it has Advanced the Important Objects Contemplated by its Founders - Lachlan, R. A. (J. C. Becket Print., 1852)
Keywords: Natural History Society

Biographical sketch of the late Daniel Arnoldi, M.D - Hall, Archibald (William Salter and Co., 1850)
Keywords: Arnoldi; Daniel; Médecine

Archéologie religieuse du diocèse de Montréal, 1850 - Viger, Jacques (Lovell & Gibson, 1850)
Keywords: Diocèse; Églises

Biographical Sketch of the Late Alexander Henry, esq. (Canadian Magazine and Literary Repository, 1824)
issued: 1824-01/1824-06
Keywords: Fourrure; Henry; Alexander; Marchands

A brief account of the fur trade to the Northwest country, carried from Lower Canada, and of the various agreements and arrangements under which it was conducted (Canadian Review and Literary and Historical Journal, 1824)
Keywords: Compagnie du Nord-Ouest; Fourrure